2009
DOI: 10.1021/ma900183p
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Hexa- and Undecablock Terpolymers with Hierarchical Molecular Architectures

Abstract: We report the synthesis, phase behavior, and viscoelastic and mechanical properties of a new type of multiblock copolymer composed of glassy poly(cyclohexylethylene) (C), semicrystalline poly(ethylene) (E), and elastomeric poly(ethylene-alt-propylene) (P). Five nearly monodisperse CECEC−P hexablock terpolymers and one (CECEC)2−P undecablock copolymer were synthesized by sequential anionic polymerization followed by catalytic hydrogenation. These multiblock copolymers, which contain equal volume fractions of P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
95
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(113 citation statements)
references
References 77 publications
16
95
1
1
Order By: Relevance
“…The perpendicular lamellar-in-lamellar structure was discovered by Fleury and Bates 7,8 in C-E-C-E-C-P terpolymers, consisting of cyclohexylethylene (C), ethylene (E), and propylene (P) blocks in ratio of 1:1:2 (see Fig. 1).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The perpendicular lamellar-in-lamellar structure was discovered by Fleury and Bates 7,8 in C-E-C-E-C-P terpolymers, consisting of cyclohexylethylene (C), ethylene (E), and propylene (P) blocks in ratio of 1:1:2 (see Fig. 1).…”
Section: Introductionmentioning
confidence: 87%
“…This phenomenon became an attractive area of research both experimentally [1][2][3][4][5][6][7][8][9][10][11][12] and theoretically, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] during the last decades. First, the two-length-scale structures, which might be called lamellar-in-lamellar structures (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies reported in the literature the two out of three or more blocks were polystyrene (PS) and a polydiene, mainly poly(butadiene) (PB) or poly(isoprene) (PI), whereas the remaining blocks were poly(2‐vinylpyridine) (P2VP), poly(ethylene oxide) (PEO), poly(dimethylsiloxane) (PDMS), or poly(methyl methacrylate) (PMMA) . Furthermore, hydrogenated derivatives of hexablock and undecablock samples [containing poly(cyclohexylethylene), poly(ethylene), and poly(ethylene‐ alt ‐propylene), which were derived from the catalytic hydrogenation of PS, PB, and PI, respectively] have also been reported . The major interest in such multicomponent systems has been the investigation of their self‐assembly in order to predict the type of phases adopted by these multicomponent materials (depending on the values of the Flory‐Huggins interaction parameter, χ , and the relative volume fractions of the blocks).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since PI 3,4 and PDMS are miscible the macromolecular architecture maybe comparable with the ABCBA linear pentablock terpolymers, which have been thoroughly investigated in the literature, especially on the effect the interaction parameter has between the different blocks on the observed final morphology . Taking into consideration the work by the Matsushita and the Bates research groups on multiblock multicomponent systems where undecablock copolymers (Matsushita) and terpolymers (Bates) have been studied it is easily understood that our approach involves the use of four blocks instead of just two or three to synthesize complex linear multiblock multicomponent systems. Our immediate future aim is to synthesize even more complex macromolecules involving additional immiscible blocks, alter the block sequence, promote the formation of new morphologies as well as to perform catalytic hydrogenation in the already prepared heptablocks in order to directly compare their behavior with the hexablock and undecablock polymers already reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Advanced development of nanotechnologies, in fields such as integrated circuit, requires fabrication of materials possessing multiple nanometer length scales . Recent efforts have been greatly devoted to create hierarchical microstructures, which is at multiple length scales, by virtue of the self‐assembly of precise building molecules . One of the building molecules concerns a linear multiblock copolymer consisting of one or two tails and many midblocks .…”
Section: Introductionmentioning
confidence: 99%